2018
DOI: 10.2196/11181
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Continuous Glucose Monitoring in Free-Living Healthy Individuals: Implications for the Use of Wearable Biosensors in Diet and Physical Activity Research

Abstract: BackgroundWearable sensors have been increasingly used in behavioral research for real-time assessment and intervention purposes. The rapid advancement of biomedical technology typically used in clinical settings has made wearable sensors more accessible to a wider population. Yet the acceptability of this technology for nonclinical purposes has not been examined.ObjectiveThe aim was to assess the acceptability of wearing a continuous glucose monitor (CGM) device among a sample of nondiabetic individuals, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 37 publications
1
24
0
1
Order By: Relevance
“…The recruitment goal for this study was to enroll 20 participants. This sample size was chosen because of the pilot nature of the study and on the basis of previous feasibility and acceptability studies that tested technology-based tools (31,32).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recruitment goal for this study was to enroll 20 participants. This sample size was chosen because of the pilot nature of the study and on the basis of previous feasibility and acceptability studies that tested technology-based tools (31,32).…”
Section: Participantsmentioning
confidence: 99%
“…In patients with type 2 diabetes, CGM-based PA counseling in intervention settings has been shown to increase PA (28,29). Incorporating CGMs into lifestyle interventions for nondiabetic individuals has also been explored (30,31). The results suggest that leveraging data from biosensors is highly promising.…”
Section: Introductionmentioning
confidence: 99%
“…CGM could therefore be another method for the passive, objective detection of meal timings in future, although further research, particularly in populations without diabetes, is required. Encouragingly pilot work in the US indicates that wearing a CGM for up to a week is as acceptable as wearing accelerometer-based sensors for 7 days ( 67 ). Furthermore, our own pilot work in the UK ALSPAC-G2 cohort demonstrated that using the latest CGM devices, which no longer require finger prick tests for calibration, improves uptake of 6 days of monitoring ( 68 ).…”
Section: When We Eatmentioning
confidence: 99%
“…Meal detection algorithms have yet to be robustly demonstrated though, and further research using CGM in populations without diabetes is required. Encouragingly, pilot work in the US indicates that wearing a CGM for up to a week is as acceptable as wearing accelerometer-based sensors for 7 days 63 . Furthermore, our own pilot work in the UK ALSPAC-G2 cohort demonstrated that using the latest CGM devices, which no longer require finger prick tests for calibration, improves uptake of 6 days of monitoring 64 .…”
Section: When We Eatmentioning
confidence: 99%